1990
DOI: 10.1099/0022-1317-71-11-2691
|View full text |Cite
|
Sign up to set email alerts
|

Definition of murine T helper cell determinants in the major capsid protein of human papillomavirus type 16

Abstract: Three murine major histocompatibility complex (MHC) class II-restricted T cell determinants were identified in the major capsid protein L1 of human papillomavirus (HPV) type 16. Peptides derived from HPV-16 L1, which contain putative T cell epitopes located by a predictive algorithm, were synthesized and tested for lymphoproliferative activity by direct immunization, followed by in vitro assay of responses to peptides or recombinant HPV-16 L1. The MHC restriction of the stimulatory peptides was determined usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

1992
1992
1997
1997

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…A major obstacle in studying CMI to HPV is the lack of a suitable culture system to propagate the virus in vitro. As a result, several investigators have used synthetic peptides de-rived from HPV type 16 (HPV-16) sequences (1,8,9,13,19,32,34,36) as well as recombinant viruses expressing HPV-16 genes (13,39) as sources of antigens for CMI assays. In this study, we used one of the commonly studied measures of CMI response, TCP response, to investigate its association with respect to detection of HPV infection and to HPV-related cervical disease.…”
mentioning
confidence: 99%
“…A major obstacle in studying CMI to HPV is the lack of a suitable culture system to propagate the virus in vitro. As a result, several investigators have used synthetic peptides de-rived from HPV type 16 (HPV-16) sequences (1,8,9,13,19,32,34,36) as well as recombinant viruses expressing HPV-16 genes (13,39) as sources of antigens for CMI assays. In this study, we used one of the commonly studied measures of CMI response, TCP response, to investigate its association with respect to detection of HPV infection and to HPV-related cervical disease.…”
mentioning
confidence: 99%
“…There is limited information on T cell responses to HPV-16 (Stranget al, 1990;Davies et al, 1990), although two groups have recently reported the response of mice to the HPV-16 E7 protein Tindle et al, 1991). The E7 molecule is important because of its proposed involvement in cellular transformation in tissue culture (Matlashewski et al, 1987;Phelps et al, 1988) and because its gene is found integrated into the DNA of a high proportion of carcinomas in which HPV DNA is present (Diirst et al, 1983;Gissmann et al, 1983Gissmann et al, , 1984.…”
mentioning
confidence: 99%
“…Although papillomavirus VLPs have been shown to assemble in diverse eukaryotic cell types (7,8,12,14,34,36), assembly has not previously been demonstrated in prokaryotes. L1 fusion proteins have mainly been expressed in bacteria (1,11,15,31), and when bona fide L1 proteins were expressed, VLP assembly was not examined (5). In this study, we have demonstrated that HPV16 VLPs do assemble in Salmonella, probably because of the high-level expression of wild-type L1 and because neither glycosylation of L1 nor eukaryotic chaperons are required for capsid assembly (46).…”
Section: Discussionmentioning
confidence: 84%